Optimal Location and Sizing of FACTS Devices to Improve Voltage Profiles on a 132 kV Mwanza-Musoma-Nyamongo Transmission Line - Manga, Fausta; Makolo, Peter; Mwasilu, Francis (Tanzania Journal of Engineering and Technology, 2025)
Recently, utility companies have desired to supply quality, stable and reliable power to customers, and ensure they meet the demand. Flexible AC Transmission Systems (FACTS) dynamic compensator devices such as Static Synchronous Compensator (STATCOM), Static VAr Compensator (SVC) and Unified Power Flow Controller (UPFC) are an impeccable choice, however, cost is one of the limiting factors following these technologies. In addition, using FACTS devices in the system requires a detailed steady state, dynamic and optimisation analysis to effectively meet the purpose and ensure reduced cost. This paper proposes using an optimised FACTS device to improve voltage profile, power transfer, system stability, and reduce system losses on 132 kV Mwanza–Musoma–Nyamongo transmission line. The analytical and Particle Swarm Optimisation technique was used to obtain the FACTS device's optimal size and location. The optimized FACTS device is incorporated in the system model and implemented using PSS/E software version 35. The model was analysed with the 132 kV MwanzaMusoma–Nyamongo transmission line loaded to its capacity, the network was observed to have an improved voltage profile, the voltage deviation lowered by 84% as compared to the current network voltage deviation of 0.2 p.u. Also, the transmission line transfer capability increased by 32 MW from the current transfer capability without distortion of the voltage profile and with an improvement on system stability. The ± 60 MVAr optimized STATCOM was observed to lower the system losses by an average of 14%. Furthermore, analysis concerning with the operation costs was observed that with maximum transfer the FACTS device investment payback period is thirteen (13) months demonstrating the system's financial viability.